A dilemma of self-interest vs. ethical responsibilities in political insider trading - Hanousek, Jan (Journal of business ethics, 2023)
Political insider trading has brought substantial attention to ethical considerations in the academic literature. While the Stop Trading on Congressional Knowledge (STOCK) Act prohibits members of Congress and their staff from leveraging non-public information to make investment decisions, political insider trading still prevails. We discuss political ethics and social contract theory to re-engage the debate on whether political insider trading is unethical and raises the issues of conflict of interest and social distrust. Empirically, using a novel measure of information risk, we find that senator trades are associated with substantially high levels of information asymmetry. Moreover, based on inside political information, senators earn significant market-adjusted returns (4.9% over 3 months). Thus, our results do not support the prediction made by social contract theory and thereby provide a potential resolution to the ongoing debate on banning stock trading for members of Congress.